Pengaruh Kecepatan Pengaduk Dan Waktu Fermentasi Terhadap Konsentrasi Bioetanol Pada Fermentasi Nira Nipah Kental Menggunakan Saccharomyces Cerevisiae - Feri Wibowo; Chairul Chairul; Irdoni S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In Riau province the existence of palm is abundant. Nipah can potentially supply biofuels because Its sap has a sugar content of 15-20% which can be converted into bioethanol. Bioethanol is ethanol produced from raw materials containing starch, sugar and cellulose through a process of fermentation and distillation that can be used as an alternative fuel which is environmentally friendly and renewable. To be Able to produce bioethanol from nypa sap in a laboratory scale, it is necessary to study the manufacture of bioethanol from nypa sap through fermentation by using Sacharomyces cerevisiae fermentation medium volume of 2 liters. The objective of the research is to convert the sugar in the nypa sap through fermentation into bioethanol and to observe the effect of stirring speed, viscosity of the juice in the fermentation medium and fermentation time on bioethanol production using Sacharomyces cereviceae. Through the process of fermentation using yeast Sacharomyces cereviceae, glucose is converted into ethanol and carbon dioxide. Preparation starter was made with yeast inoculum process Sacharomyces cereviceae at 10% of the yeast fermentation medium, therefore it can be adaptable and ready for fermentation. Fermentation takes place in batches with a volume of 2 liters of fermentation medium, stirring speed variation of 150, 200, 250 rpm and viscosity sap by evaporation at 20% (v/v) as well as variations in the fermentation time of 24, 36, 48, 60 and 72 hours. Temperature fermentation at room temperatur is 25 – 30oC. Ethanol concentration was Analyzed by using Gas Chromatography. The optimum fermentation process is shown in the stirring speed of 200 rpm with sap viscosity of 20% (v/v) and fermentation hours 36th, therefore it was obtained 15,407% (v/v) or 121,604 mg/ml.Keywords: bioethanol, condensed sap, nypa sap, saccharomyces cerevisiae, stiriing speed.